CLASS ACTIONS IN QUEBEC: HIGHLIGHTS OF A UNIQUE PROCEDURE - Piché, Catherine (Revista Eletrônica de Direito Processual, 2021)
This article highlights the class action proceeding in Quebec, seeking to expose its main characteristics. The article initially explores the Canadian legal system and provincial legislative peculiarities. In addition to that, the paper explores the three major objectives of class actions: (i) judicial economy; (ii) maximizing access to justice; (iii) deter actual and potential wrongdoers from inflicting damage, especially small amounts of damage on a larger number of people (preventative objective). In sequence, such article specifies how the two-step class action procedure works, starting with the application for authorization, which is a preliminary request and a unique step in the province of Quebec that is meant to filter frivolous demands.Only once the authorization is granted may the case be heard collectively on the merits. The second step of the two-step procedure is an originating application that must be filed if the class action is authorized. Furthermore, this study deals with many relevant matters regarding the class actions in Canada (particularly Quebec), such as: (i) Right of Appeal; (ii) Res Judicata Effect – on absent members; (iii) Monetary Distributions and Types of Collective Recovery; (iv) Class Action Financing; (v) Possible Settlements; (vi) Multi-Provincial Class Proceedings and National Classes.